Daily clinical dose (D) poorly predicts trough serum methadone concentration (ctrough) in patients undergo methadone maintenance therapy (MMT) with good adherence - Mohamed Nazar, Nor Ilyani; Sim, Hann Liang; Tan, Soo Choon; Ismail, Rusli; Musa, Ramli; Abu Bakar, Ahmad Zafri (R. S. Publication, 2014)
Methadone maintenance therapy (MMT) has been used for opioid dependence as one of the harm-reduction approaches. It is also effectiveindirectlyto prevent the wide spread of HIV-related risks such as needle sharing behaviour and illicit drug use. With low costs calculated per patient, MMT has been put as top priorities on reducing opioid dependencies in Malaysia. However, the effective dose strategy of the therapy is still open to debate. The study aimed to investigate the potential of methadone trough concentration (Ctrough)tobe a surrogate marker for such purpose. We conducted a 9-months prospective study to assess the relationship between Ctrough and Dose (D) of methadone. A total of 115 subjects fulfilled the inclusion criteria and had given their consents to participate. Two (2) ml of the trough blood samples (Ctrough) were taken and centrifuged within 4 hours from the time taken at 5,000 Gfor 5 minutes. The resulting serum samples were kept at -20°C until further analysis. The methadone concentration was determined by using a validated method for Methadone ELISA kit. The patients were subjected to another 2 follow ups at 3 months interval each and the same method of serum sampling was applied. Initial correlation reveals significant positive correlation between the two variables in every follow up, ranging between r=0.403-0.419 (p<0.005). Further regression analysis reveals that the coefficient of determination, r2 was poor with only 15-17% of variation in the Ctrough can be explained by the changes in clinical doses (p<0.005). Based on the results, we conclude that daily clinical dose poorly predicts methadone Ctrough for the purpose of dosing adjustment and monitoring of therapy.